Coworking Spaces: A Source of Social Support for Independent Professionals - Gerdenitsch, Cornelia; Scheel, Tabea E.; Andorfer, Julia; Korunka, Christian (Frontiers in Psychology, 2016)
Coworking spaces are shared office environments for independent professionals. Such spaces have been increasing rapidly throughout the world, and provide, in addition to basic business infrastructure, the opportunity for social interaction. This article explores social interaction in coworking spaces and reports the results of two studies. Study 1 (N = 69 coworkers) finds that social interaction in coworking spaces can take the form of social support. Study 2 further investigates social support among coworkers (N = 154 coworkers) and contrasts these results with those of social support among colleagues in traditional work organizations (N = 609). A moderated mediation model using time pressure and self-efficacy, based on the conservation of resources theory, is tested. Social support from both sources was positively related to performance satisfaction. Self-efficacy mediated this relationship in the employee sample, while in the coworking sample, self-efficacy only mediated the relationship between social support and performance satisfaction if time pressure was high. Thus, a mobilization of social support seems necessary in coworking spaces. We conclude that coworking spaces, as modern social work environments, should align flexible work infrastructure with well-constructed opportunities for social support.